Association of periampullary diverticulum types with post-ERCP hyperamylasemia: a retrospective observational study - Serdar Akca; Galip Egemen Atar; Serkan Ocal; Osman Cagin Buldukoglu; Gokhan Koker; Muhammed Devran Isik; Besir Kaya; Hatice Deniz; Ferda Akbay Harmandar; Ayhan Hilmi Cekin (BMC Gastroenterology)
Abstract Background This study aimed to assess the prevalence of periampullary diverticulum (PAD) among endoscopic retrograde cholangiopancreatography (ERCP) patients in Southwestern Turkey and investigate the association between the new PAD classification, post-ERCP hyperamylasemia, and post-ERCP pancreatitis (PEP). Materials and methods We retrospectively reviewed 1,317 ERCP procedures performed between January 1, 2022, and December 31, 2023, at Antalya Training and Research Hospital. The PAD type was determined according to the He-xian Shi classification. Hyperamylasemia was defined as an increase of three times the normal level of amylase at 4 to 6 h, and PEP was defined as hyperamylasemia along with abdominal pain lasting more than 24 h. Results A total of 594 naive patients who underwent ERCP were analyzed. PAD was present in 137 patients (23.1%), and the success rate of choledochal cannulation in the first ERCP procedure was 94.3%. There was no difference in the choledochal cannulation rate between patients with and without PAD (95.6%-93.4%, p = 0.59). Asymptomatic hyperamylasemia was observed in 19.3% of the patients. Post-ERCP hyperamylasemia rates were similar between patients with and without PAD (17.5% and 21.2% respectively, p = 0.31). PEP was observed in 8.0% of the patients. Presence of PAD was not a risk factor for post-ERCP pancreatitis (7.3% compared to 8.8%, p = 0.82). When we checked the results according to the type of PAD, the prevalence of post-ERCP hyperamylasemia was significantly lower in patients with type 2b PAD than in those with type 1 and type 2a patients. Conclusion PAD is a common finding in ERCP patients, with a prevalence of 23.1% in our cohort. The rate of choledochal cannulation, post ERCP hyperamylasemia and PEP did not differ between the patients with and without PAD. However, the type of PAD is important; post-ERCP hyperamylasemia is significantly lower in patients with type 2b than in type 1 and type 2a PAD patients. Different subtypes of PAD may have different associations on ERCP outcomes. Further investigations with refined and standardized PAD classification systems are needed.